Influence of Brand Experience, Customer Satisfaction, And Trust On Customer Loyalty for Kanzler Crispy Nugget Products In Sragen Regency - Geddy Ganjar Pramana; Muhammad Imron; Ahadiati Rohmatiah (Citakonsultindo, 2026)
This study aims to examine and analyze the influence of brand experience, customer satisfaction, and trust on customer loyalty for Kanzler Crispy Nugget products in Sragen Regency. The sampling technique used the Lemeshow formula approach with a total sample of 100 customer respondents. Data collection methods were carried out through questionnaires, while data analysis used multiple linear regression, t-test (partial), F-test (simultaneous), and the coefficient of determination (R2) assisted by the SPSS program. The results of data analysis and discussion show that partially, the variables of brand experience, customer satisfaction, and trust each have a positive and significant influence on customer loyalty. Furthermore, the simultaneous test results prove that the three independent variables collectively have a significant effect on the formation of customer loyalty. The conclusion of this study confirms that enhancing the brand interaction experience, satisfaction with product quality, and consumer trust is empirically proven to be the determining factor in driving repurchase loyalty for Kanzler Crispy Nugget products in the region.